Shuffle-induced modulated structure and heating-induced ordering in the metastable β-titanium alloy, Ti-5Al-5Mo-5V-3Cr. (February 2020) - Zheng, Yufeng; Antonov, Stoichko; Feng, Qiang; Banerjee, Rajarshi; Banerjee, Dipankar; Fraser, Hamish L.
Abstract: A nano-scaled shuffle-induced modulated structure and heating-induced ordering have been characterized in a metastable β-titanium alloy, Ti-5Al-5Mo-5V-3Cr, and their inter-relationship was investigated through in-situ and ex-situ conventional and aberration-corrected scanning/transmission electron microscopy and atom probe tomography. The nano-scaled O′ phase with a disordered orthorhombic-modulated structure formed by the 011 < 01 1 ¯ > β transverse phonon was characterized for the first time to be stable from room temperature to ∼200 °C. The O″ phase with an ordered orthorhombic structure formed from the β phase during aging above the O′ phase solvus temperature, where Al segregation in nano-scaled regions led to ordering of every third 011 planes. Graphical abstract: Image, graphical abstract